Structural and optical properties of RF-sputtered Ge thin films using magnetron sputtering technique - Ariffin, Nurul Assikin (2018)
The desire to control germanium (Ge) thin film quality while keeping it cost effective has become one of the biggest challenges. This thesis proposes radio frequency (RF) magnetron sputtering as a technique to deposit Ge thin films (towards nanowires growth) on a glass substrate at room temperature. This research focuses on the structural and optical properties of Ge thin films by varying the pressure and RF power. The structural properties were characterized using atomic force microscopy (AFM), high surface profilometer, and x-ray diffraction (XRD). Meanwhile, the optical properties were investigated using ultraviolet-visible spectroscopy (UV-Vis) and Raman spectroscopy. Based on the study, at a high pressure of 15 mTorr, the thickness obtained was 114.76 ± 2.89 nm for the as-deposited Ge thin film. This is due to the bombardment of the atom during the sputtering process caused the thickness to decrease as the pressure was increased. Meanwhile, at a higher RF power of 100 Watt, the thickness obtained was found to increase to 232.32 ± 5.67 nm. This was caused by the atoms that gained more kinetic energy to be bombarded onto the glass substrate when the RF power was increased. The AFM studies show that the lowest root-mean-square (rms) surface roughness obtained the in lowest pressure of 5 mTorr was 1.898 nm. On the other hand, at 50 Watt of RF power, the lowest rms surface roughness obtained was 10.283 nm. Moreover, based on the band gap energy analysis using UV-Vis, values obtained were in the range of 3.84 to 3.91 eV. Besides, the phase analysis using XRD also shows all the deposited Ge thin films obtained were in an amorphous phase. In addition, Raman analysis also shows second-order Ge phonon modes at the region of 535 to 610 cm-1 which tend to shift due to its amorphous behavior. The heat treatment was applied at a different annealing temperature of 280 ˚C and 450 ˚C in order to recover and alter the microstructure of Ge thin film. The thickness was found to be increased from 40.53 ± 2.026 nm to 126.06 ± 6.378 nm as the pressure was increased when the thin films were annealed at a temperature of 280 ˚C. Meanwhile, at annealing temperature of 450 ˚C, the thickness of thin films decreased from 148.76 ±7.4 nm to 69.83 ± 3.471 nm as the pressure was increased. In comparison, when the annealing process was applied, the thickness increased as the RF power was increased in both of the annealing temperatures of 280 ˚C and 450 ˚C from 102.07 ± 5.12 nm to 137.43 ± 5.471 nm and 76.46 ± 3.387 nm to 177.43 ± 6.832 nm, respectively. In this study, it is found that the most optimized Ge thin film was from annealed Ge thin film at temperature of 450 ˚C with a thickness of 148.76 ±7.4 nm and the rms surface roughness of 1.898 nm, which was deposited at a lower pressure and RF power of 5 mTorr and 25 Watt, respectively. This shows that the deposition parameters influence the surface morphology, phase, band gap energy, and phonon modes of Ge thin films. By controlling these parameters, Ge thin films surface morphology can be optimized, thus producing low rms surface roughness. The development of Ge thin films as the high-quality film might be useful in the future especially in the growth of nanowire for solar cell application.